Implementasi Pemikiran Ki Hadjar Dewantara dalam Mengelola Lembaga Pendidikan - Bradley Setiyadi; Rahmalia Rahmalia (SAP (Susunan Artikel Pendidikan), 2022)
This study aims to determine the application of Ki Hadjar Dewantara's thinking in managing educational institutions at the Sekolah Taman Budaya Jambi. Ki Hadjar Dewantara's thoughts on education have become the image of the history of education in Indonesia. The concept of education features the uniqueness of Indonesian culture and emphasizes the importance of processing potentials students in an integrated manner. In the management of educational institutions, the Sekolah Taman Budaya, which adopts the management of the Perguruan Taman Siswa, of course refers to the effort to refer to the Panca Dharma Pendidikan Taman Siswa and Pratap Triloka and synergizes with parents and the community through the Tri Pusat Pendidikan. This study limits the problem to the management of educational institutions that apply one of Ki Hadjar Dewantara's thoughts, namely Panca Dharma Pendidikan Taman Siswa. The research subject is the manager of the Sekolah Taman Budaya School. The object of the research is the application of Ki Hadjar Dewantara's thinking in the management of the Sekolah Taman Budaya. The method used in this research is qualitative method. The results of this study indicate that the thoughts of Ki Hadjar Dewantara which are expressed in the three educational philosophies and Panca Dharma are well implemented by the Sekolah Taman Budaya.